2023
DOI: 10.1097/dcr.0000000000002673
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis: Selective Use of Neoadjuvant Chemoradiation in Locally Advanced Rectal Cancer

Abstract: BACKGROUND:Locally advanced rectal cancer has high cure rates with trimodal therapy. Studies sparing neoadjuvant chemoradiation in selected patients show comparable outcomes. OBJECTIVE:This study aimed to determine the cost-effectiveness of selective use of neoadjuvant chemoradiation in this population. DESIGN: A cost-effectiveness analysis model compared selective and blanket use chemoradiation for locally advanced rectal cancer. SETTINGS: Literature review, expert consensus, and a prospective database popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 24 publications
2
3
0
Order By: Relevance
“…Differences occurred from various model's specifications, as we applied specific utilities and transition probabilities from the ARO-04 trial [35,42] for the base case. NOM was dominant over resection in concordance with other cost-effectiveness simulations [10][11][12][13][14]49]. The model appeared to be insensitive to changes in treatment costs or QALYs in one-way exploratory sensitivity modeling, suggesting that NOM (I) remained the preferred treatment option regarding the patient's costs and QoL even with varied parameters.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Differences occurred from various model's specifications, as we applied specific utilities and transition probabilities from the ARO-04 trial [35,42] for the base case. NOM was dominant over resection in concordance with other cost-effectiveness simulations [10][11][12][13][14]49]. The model appeared to be insensitive to changes in treatment costs or QALYs in one-way exploratory sensitivity modeling, suggesting that NOM (I) remained the preferred treatment option regarding the patient's costs and QoL even with varied parameters.…”
Section: Discussionsupporting
confidence: 74%
“…We found that both treatment options are cost-effective for the underlying WTP, but NOM (I) was more cost-effective in each simulated case. The simulated effectiveness was comparable with values reported in the literature [10][11][12][13][14]49]. Differences occurred from various model's specifications, as we applied specific utilities and transition probabilities from the ARO-04 trial [35,42] for the base case.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Surgical complications were reduced and the 3-year survival rate improved compared with historical controls receiving neoadjuvant chemoradiation. Mueller et al 11 reported a cost-effectiveness analysis of selective versus “blanket” use of chemoradiation for LARC and showed that selective use is associated with both higher quality-adjusted disease-free life years and lower cost.…”
Section: Selective Use Of Neoadjuvant Radiation and Chemoradiationmentioning
confidence: 99%